2016
DOI: 10.1063/1.4964094
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the cubic to tetragonal phase transition in methylammonium lead iodide perovskite

Abstract: Hybrid organic-inorganic perovskites, as well as the perovskites in general, are known for their phase complexity evidenced by the stabilization of different polymorphs, and thus an understanding of their regions of stability and transitions can be important for their photovoltaic and optoelectronic technologies. Here we use a multiscale approach based on first-principles calculations with van der Waals corrections and classical force-field molecular dynamics to determine the finite-temperature properties of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 72 publications
7
51
0
Order By: Relevance
“…First Cycle: On the first heating stage, in Figure 8a, the intensity of the strongest satellite decreases to zero only above 346 K, indicating that at this temperature only the cubic phase is expected. [30] However, in conformity with Tyson et al, [32] we observed a pseudocubic unit cell in the whole 310-350 K range. Another degenerate case, when α ¼ γ ¼ 0.5, was observed below 315 K during the first thermal cycle heating stage.…”
Section: X-ray Datasupporting
confidence: 92%
See 1 more Smart Citation
“…First Cycle: On the first heating stage, in Figure 8a, the intensity of the strongest satellite decreases to zero only above 346 K, indicating that at this temperature only the cubic phase is expected. [30] However, in conformity with Tyson et al, [32] we observed a pseudocubic unit cell in the whole 310-350 K range. Another degenerate case, when α ¼ γ ¼ 0.5, was observed below 315 K during the first thermal cycle heating stage.…”
Section: X-ray Datasupporting
confidence: 92%
“…The high‐temperature transition results in the reduction of the unit cell in the c ‐direction and could be driven by an instability of the crystal with respect to the emergence of a particular phonon mode . This hypothesis is supported by the theoretical work of Saidi and Choi, in which the stabilization of the cubic phase is explained through vibrational energy and entropy considerations.…”
Section: Resultsmentioning
confidence: 80%
“…1. These low-frequency phonon modes are the optical phonons contributed by the inorganic Pb-I lattice (35,36). On the other hand, the absence of appreciable peaks in the 150 to 3500 cm −1 range indicates that MA molecular vibrations are not coupled with the CBM, the VBM, or defect states.…”
Section: Resultsmentioning
confidence: 96%
“…Thermal stability is a very important criterion for the commercialization of OIHP‐based solar cells. The OIHP usually undergoes degradation or phase transformation under long‐term high‐temperature stress . The thermal instability of PSCs can be mainly ascribed to the low thermal conductivity of the OIHP layer.…”
Section: The Stability Of Organic–inorganic Halide Lead Perovskitesmentioning
confidence: 99%
“…www.advancedsciencenews.com www.entechnol.de vibrational, and thermodynamic properties of MAPbI 3 , confirming the tetragonal to cubic at T ¼ 327 K driven largely by phonon modes associated with the inorganic lattice. [26,37] The configurational disorder associated with the organic molecule has very little effect on this transition. Table 1 describes the phase transition parameters of a CH 3 NH 3 SnCl 3 compound.…”
Section: Phase Stabilitymentioning
confidence: 99%